2018
DOI: 10.5194/hess-2018-5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydroclimatic control on suspended sediment dynamics of a regulated Alpine catchment: a conceptual approach

Abstract: Abstract.We analyse the control of hydroclimatic factors on suspended sediment concentration (SSC) in Alpine catchments by differentiating among the potential contributions of erosion and suspended sediment transport driven by erosive rainfall, defined as liquid precipitation over snow free surfaces, icemelt from glacierized areas, and snowmelt on hillslopes. We account for the potential impact of hydropower by intercepting sediment fluxes originated in areas diverted to hydropower reservoirs, and by consideri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…But in general, for every watershed and sediment type, it is likely that both a and b will be different. For example, Costa 12 found a = 0.56 and b = 1.25 in their investigated alpine catchment whereas Felix 54 found a = 0.59 and b = 1 in their HPP storage tunnel. In our case, at larger SSCs the relationship diverges from linearity (Fig.…”
Section: Calibration Of New Sensor To Sscmentioning
confidence: 95%
See 1 more Smart Citation
“…But in general, for every watershed and sediment type, it is likely that both a and b will be different. For example, Costa 12 found a = 0.56 and b = 1.25 in their investigated alpine catchment whereas Felix 54 found a = 0.59 and b = 1 in their HPP storage tunnel. In our case, at larger SSCs the relationship diverges from linearity (Fig.…”
Section: Calibration Of New Sensor To Sscmentioning
confidence: 95%
“…High resolution estimates of SSC can be used to quantify human effects on sediment production, for example the effects of dam construction and erosion control 8,9 , the natural erosion gradients over entire mountain ranges 10 , the role of sampling in global erosion rates 11 , and many others. Measurements of SSC at a basin outlet can give us a basin-integrated picture of possible hydroclimatically-driven sources of sediment, like rainfall erosion, snowmelt hillslope erosion, glacier ice melt erosion, even hydropower storage in dams 12 . These measurements of SSC are also important for understanding the impact of hydroclimatic forcing on activating sediment sources and transport dynamics, and physically-based modelling thereof [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The sediment dynamics will be different, however [56]. A study on the upper Rhône catchment demonstrated that the SSC-Q relationships were not capable of reproducing probability distribution functions of SSC because they neglect physical processes that govern seasonal patterns of SSC, especially in summer [17]. Instead, a non-linear multi-variate rating curve performed fairly well, although it does not use discharge at all, but includes the input variables mean daily rainfall, ice melt, snow melt over unregulated areas, and release from reservoirs, which are governing the changes in SSC.…”
Section: Sustainability 2018 10 X For Peer Review 7 Of 16mentioning
confidence: 99%
“…[10] or Ref. [17], for example, taking variables and processes such as rainfall, coverage with erodible soils and vegetation, glacier length change or snow and ice melt into account. Once the sediment input into the reservoir has been estimated, the well-known relationship of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these studies examined the annual changes, some studies employed event scale data to analyse suspended sediment dynamics and their responses to climate change and land surface changes (Gao, Fu, et al, 2018; Horowitz, 2003; López‐Tarazón et al, 2009). Event rainfall amount, rainfall intensity and antecedent rainfall variables have been widely used to provide insights into event characteristics and spatiotemporal variations in hydrological processes (Ahn et al, 2017; Costa et al, 2018; Fang, Shi, et al, 2011; Gao, Fu, et al, 2018; López‐Tarazón et al, 2009; Zhang et al, 2018; Zhang, Chen, et al, 2019; Zhang, Zhao, et al, 2019). Different regression models have been developed to quantify the relationship between suspended sediment concentration (SSC) and runoff (Q) (Costa et al, 2018; Zheng, 2018).…”
Section: Introductionmentioning
confidence: 99%